Peculiarities Of Postoperative Rehabilitation In Children After Surgical Treatment Of Congenital Heart Disease - Shpak, Ekaterina Dmiriyevna; Hasanova, Aishat Imamguseynovna; Usmanova, Maryam Lom-Alievna; Said-Eminov, Zubair Yunadievich; Ibragimova, Zaynam Murtuzalievna; Osmanova, Djamilya Arsanalievna; Magomedova, Mariyat Magomedovna (Journal of Neonatal Surgery, 2025)
The paper considers theoretical and practical aspects of postoperative rehabilitation of children with congenital heart disease. The study reflects the peculiarities of the dynamics of medical indicators and psychological factors affecting the effectiveness of recovery in the long term. The analysis of statistical data for the period 2019-2024, a sociological study with the participation of parents of operated children is carried out, the assessment of economic costs of rehabilitation measures is presented. Practical recommendations for optimizing the system of care and improving the quality of life of patients are proposed. The results of the study indicate the high significance of an integrated approach including medical, socio-psychological and pedagogical components